2019
DOI: 10.3390/ijms20215518
|View full text |Cite
|
Sign up to set email alerts
|

First Insights on the Presence of the Unfolded Protein Response in Human Spermatozoa

Abstract: The unfolded protein response (UPR) is involved in protein quality control and is activated in response to several stressors. Although in testis the UPR mechanisms are well described, their presence in spermatozoa is contentious. We aimed to investigate the presence of UPR-related proteins in human sperm and the impact of oxidative stress induction in UPR activation. To identify UPR-related proteins in human sperm, a bioinformatic approach was adopted. To explore the activation of UPR, sperm were exposed to hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Recent evidence suggests that mammalian spermatozoa may possess an unfolded protein response (UPR); a conserved cellular pathway that is activated upon accumulation of unfolded or misfolded proteins during stress conditions [126]. The activation of the UPR triggers the expression of chaperones to assist protein refolding (reviewed in [127]), whilst also blocking the synthesis of other proteins via the phosphorylation of eukaryotic translation initiation factor-2 (eIF2α) [128].…”
Section: Defects In the Sperm Motility Apparatus And Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence suggests that mammalian spermatozoa may possess an unfolded protein response (UPR); a conserved cellular pathway that is activated upon accumulation of unfolded or misfolded proteins during stress conditions [126]. The activation of the UPR triggers the expression of chaperones to assist protein refolding (reviewed in [127]), whilst also blocking the synthesis of other proteins via the phosphorylation of eukaryotic translation initiation factor-2 (eIF2α) [128].…”
Section: Defects In the Sperm Motility Apparatus And Signaling Pathwaysmentioning
confidence: 99%
“…The activation of the UPR triggers the expression of chaperones to assist protein refolding (reviewed in [127]), whilst also blocking the synthesis of other proteins via the phosphorylation of eukaryotic translation initiation factor-2 (eIF2α) [128]. Santiago et al [126] have reported increased levels of proteins involved in the UPR (heat shock proteins; HSF1, HSP90, HSPD1, HSP27; and eIF2α) and reduced motility in human spermatozoa exposed to H 2 O 2 . Despite this, it is possible that prolonged OS within the testes can compromise the UPR owing to 4HNE adduction of key elements of this pathway including the 60 kDa Heat Shock Protein, Mitochondrial (HSPD1) [22].…”
Section: Defects In the Sperm Motility Apparatus And Signaling Pathwaysmentioning
confidence: 99%
“…The sperm proteome was recently extracted, using the PubMed database, by Santiago et al [83]. To avoid redundancy, from the total list of sperm proteins, we excluded duplicates and only reviewed proteins (annotated using the UniProtKB/Swiss-Prot accession number) were considered (electronic supplementary material, table S2).…”
Section: Proteomic Comparisonmentioning
confidence: 99%
“…To avoid redundancy, all DEPs were mapped in the UniProt database (downloaded on May 26th, 2020) and annotated using the UniProtKB/Swiss-Prot accession number. Then, the UniProt lists were cross-compared with human spermatozoon proteome ( Santiago et al, 2019 ) through a Venn diagram analysis using the JVenn tool ( Bardou et al, 2014 ). Only proteins with a reviewed status and previously reported in human spermatozoon were used for further analysis.…”
Section: Methodsmentioning
confidence: 99%